2020
DOI: 10.1002/glia.23927
|View full text |Cite
|
Sign up to set email alerts
|

Glial endozepines and energy balance: Old peptides with new tricks

Abstract: The contribution of neuroglial interactions to the regulation of energy balance has gained increasing acceptance in recent years. In this context, endozepines, endogenous analogs of benzodiazepine derived from diazepam‐binding inhibitor, are now emerging as major players. Produced by glial cells (astrocytes and tanycytes), endozepines have been known for two decades to exert potent anorexigenic effects by acting at the hypothalamic level. However, it is only recently that their modes of action, including the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 109 publications
(223 reference statements)
0
25
0
Order By: Relevance
“…Acyl-coenzyme A binding protein (ACBP), also called diazepam-binding inhibitor (DBI) is a phylogenetically ancient protein with two distinct functions 1 , 2 . As an intracellular protein, ACBP/DBI binds, buffers and transports medium-size acyl-coenzyme A molecules, hence contributing to lipid metabolism 3 , 4 . As an extracellular protein, ACBP/DBI binds to γ-aminobutyric acid (GABA) receptors of the A type (GABA A R) 5 , 6 , and at least within the central nervous system, to other neurotransmitter receptors (such as the ODN receptors) as well 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acyl-coenzyme A binding protein (ACBP), also called diazepam-binding inhibitor (DBI) is a phylogenetically ancient protein with two distinct functions 1 , 2 . As an intracellular protein, ACBP/DBI binds, buffers and transports medium-size acyl-coenzyme A molecules, hence contributing to lipid metabolism 3 , 4 . As an extracellular protein, ACBP/DBI binds to γ-aminobutyric acid (GABA) receptors of the A type (GABA A R) 5 , 6 , and at least within the central nervous system, to other neurotransmitter receptors (such as the ODN receptors) as well 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…As an extracellular protein, ACBP/DBI binds to γ-aminobutyric acid (GABA) receptors of the A type (GABA A R) 5 , 6 , and at least within the central nervous system, to other neurotransmitter receptors (such as the ODN receptors) as well 7 , 8 . Hence, ACBP/DBI participates in paracrine and neuroendocrine signaling 4 .…”
Section: Introductionmentioning
confidence: 99%
“…22 Nevertheless, a cross-talk between circulating DBI and the central nervous system concerning the control of energy balance is conceivable, and it is likely that DBI reaches the glial cells as well as hypothalamic regions involved in feeding behavior located outside the blood-brain barrier through so far undefined mechanisms. 23 The lower fat mass exhibited by SGA infants in late infancy could result from an impaired adipogenesis. We recently reported that GPR120 -a key regulator of adipogenesis-is hypermethylated in cord blood of SGA newborns and also in peripheral blood at age 1 year and is associated with lower fat mass at the age of 1 and 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…These isoforms may play a role in receptor-mediated leptin transport from the AP to the NTS [19]. More recently, vagliocytes were reported to express octadecaneuropeptide (ODN), a glial anorexigenic peptide [42]. By contrast, AP is virtually devoid of GFAP+ astrocytes.…”
Section: Cellular Diversity and Glial Organization Within The Adult Dvcmentioning
confidence: 99%
“…Endozepines are well known endogenous ligands of benzodiazepine (BZ) receptors (see [130] for review). Over the last two decades, evidence has accumulated that strongly suggests that endozepines could act as endogenous modulators of energy balance by acting at the hypothalamic level [42,130]. The icv injection of ODN dose-dependently reduced food intake in fasted and ad libitum-fed rodents [131][132][133][134][135].…”
Section: Modulation Of Food Intake and Weight Gain By Dvc Glial Cellsmentioning
confidence: 99%